Capital Structure: An Empirical Study of the Main Colombian Airlines - Vergara-Garavito, Judith Cecilia; Durán-Parra, Heyber Daney; Figueroa-López, Greyz Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The competitiveness of the market has led the different airlines to rethink their capital structure to achieve a combination of debt and equity, which allows them to obtain higher profitability. This research aims to identify the determinants of the capital structure and establish which theory explains in better way financing decisions in six Colombian airlines that transport passengers. To this end, a data panel regression was used with a fixed-effects model, considering semiannual information collected between 2012 and 2017. The results show that operational profitability, growth, asset structure and company size are the main determinants of the capital structure, aligning this with what is indicated in the trade off theory and the pecking order theory.